Valuing floodplain protection and avoidance in a coastal watershed. Issue 4 (2nd September 2019) - Blessing, Russell; Brody, Samuel D.; Highfield, Wesley E.
Abstract : Flood‐related losses in the United States are increasing despite large‐scale mitigation efforts. To offset the rising cost of floods, the US Congress passed legislation in 2014 that will augment insurance premiums to make the National Flood Insurance Program more actuarially sound. Consequently, there is interest in lowering flood‐related costs to the homeowner, both in terms of premiums and damage. This study addresses the issue by integrating premium savings and damages avoided based on several mitigation scenarios. Specifically, it examines how much policyholders within a watershed near Houston, Texas, could have saved between 1999 and 2009 had their communities introduced specific avoidance‐based mitigation activities. The results indicate that homeowners and communities can offset premium rises and a majority of the damage suffered through marginal expansions of such initiatives. However, the costs associated with their implementation could counter some of these savings, and hence they need to be considered in future work.